The problem of aircraft technical operation control on the basis of incomplete information - Комаров, A. A.; Василенко, В. А.; Салимов, P. M. (Proceedings of National Aviation University (archive), 1998)
Considered are the methods of analysis of complex systems operation the building of mathematical models of which are supposed the formalization of process. Offered is the mathematical scheme reflecting structural and functional regularities of development in the complex systems